If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -2(x + 5) = 4(2x + -1) Reorder the terms: 8 + -2(5 + x) = 4(2x + -1) 8 + (5 * -2 + x * -2) = 4(2x + -1) 8 + (-10 + -2x) = 4(2x + -1) Combine like terms: 8 + -10 = -2 -2 + -2x = 4(2x + -1) Reorder the terms: -2 + -2x = 4(-1 + 2x) -2 + -2x = (-1 * 4 + 2x * 4) -2 + -2x = (-4 + 8x) Solving -2 + -2x = -4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2 + -2x + -8x = -4 + 8x + -8x Combine like terms: -2x + -8x = -10x -2 + -10x = -4 + 8x + -8x Combine like terms: 8x + -8x = 0 -2 + -10x = -4 + 0 -2 + -10x = -4 Add '2' to each side of the equation. -2 + 2 + -10x = -4 + 2 Combine like terms: -2 + 2 = 0 0 + -10x = -4 + 2 -10x = -4 + 2 Combine like terms: -4 + 2 = -2 -10x = -2 Divide each side by '-10'. x = 0.2 Simplifying x = 0.2
| 5x-1=4x+9 | | 8(5n+7)=216 | | 4=p-2 | | -5+x=-3 | | 16=4a+8+4a | | 6x+4=2(x-6) | | 8a^2-4d=60 | | 15x-7x=-52-5x | | 12x^2-33x+18=0 | | 8y^2+26y=-15 | | 5m+1-8m=22 | | 1m/9+10=16 | | M+4=20+3m | | 10x-35=5x+25 | | 3(4k+8)-2(2k+3)-14k= | | 8(y-5)=6y-19 | | 3x-9=x+15 | | 67*2(56+6)-(-7+7)= | | -7x+4x+15-8x= | | 6x-177=96-7x | | 6x+8=2x+24 | | P-15=-12 | | a^9+2a^8b-3a^7b^2=0 | | -30-7x=-11x+66 | | 3x-2=x+14 | | 8(6+r)=40 | | m^2-2m+1=0 | | -10x-141=-x+84 | | v^2+2v+6=0 | | (x-7)(2x+10)=0 | | 1.34x-2.71=1.67 | | 4x+2=x+14 |